Empathetic Computers: The Problem of Confusing Persons and Things. Issue 1 (March 2015) - Herzfeld, Noreen
Abstract: As computers become both more intelligent and ubiquitous we increasingly rely on them for forms of companionship. We are relational beings, instinctively drawn to those who relate back to us, an instinct that is rooted in our creation in the image of a triune, and thus relational, God. Relationships with computers, which necessarily displace relationships with other humans, have so far been shown to be dissatisfying. This dissatisfaction arises because a computer cannot be truly empathetic. It cannot feel emotion due to its lack of a body; it can only simulate emotion. This makes relationship with a computer similar to relationship with a sociopath and can isolate us from both others and our true selves.